An Analysis of The Effects of Service Features, Halal Awareness, And Underst Anding About Islamic Consumption on Purchase Decisions - Fauzi, Muhammad Fiqri; Ika Khusnia Anggraini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The rapid growth of technology has had a significant impact on consumer behavior, especially among Generation Z, who tend to use e-commerce platforms as one of the main means of shopping. In Malang City, according to the 2020 population census, Generation Z dominates, comprising 26% of the total population. This research aims to determine the influence of service features, halal awareness, and understanding of Islamic consumption on the purchasing decisions of Generation Z in Malang City on the Shopee e-commerce platform. The research method employs descriptive quantitative methods with data collection techniques through the distribution of questionnaires to 100 research samples. The test results indicate that simultaneously, the variables of service features, halal awareness, and understanding of Islamic consumption significantly influence purchasing decisions on the Shopee e-commerce platform by Generation Z in Malang City. Abstrak Pesatnya pertumbuhan teknologi memberikan dampak yang signifikan terhadap perilaku konsumen, terutama di kalangan Generasi Z yang cenderung menggunakan platform e-commerce sebagai salah satu sarana utama berbelanja. Di Kota Malang, menurut sensus penduduk tahun 2020, Generasi Z mendominasi dengan jumlah 26% dari total penduduk. Penelitian ini bertujuan untuk mengetahui pengaruh fitur layanan, kesadaran halal, dan pemahaman konsumsi Islami terhadap keputusan pembelian Generasi Z di Kota Malang pada platform e-commerce Shopee. Metode penelitian yang digunakan adalah metode deskriptif kuantitatif dengan teknik pengumpulan data melalui penyebaran kuesioner kepada 100 sampel penelitian. Hasil pengujian menunjukkan bahwa secara simultan variabel fitur layanan, kesadaran halal, dan pemahaman konsumsi Islami berpengaruh signifikan terhadap keputusan pembelian pada platform e-commerce Shopee oleh Generasi Z di Kota Malang.